2011
DOI: 10.1117/12.875035
|View full text |Cite
|
Sign up to set email alerts
|

Low noise Raman lasers for yellow-orange spectrum coverage

Abstract: Diode lasers have been demonstrated to operate over a great part of the visible spectrum: InGaN diodes cover the violetblue-green part (<530 nm) and InGaAlP diodes cover the red part (>635 nm). Some fluorophorus in biotechnology applications are excited by intermediate wavelengths, from 540 to 630 nm. Optically pumped InGaAs lasers were demonstrated from 460 nm up to 580 nm. Standard frequency doubled diode pumped solid state (DPSS) lasers lack of suitable transition to cover the 565-650nm region. It is possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…Shortly thereafter, they demonstrated a 586.5 nm CW yellow source based on self-Raman laser operation in Nd:GdVO 4 [16,17]. Recently N. Landru et al reported low noise Raman lasers for yellow-orange spectrum coverage from 556 nm up to more than 610 nm [18]. But because of the high SRS threshold, the CW intracavity SRS yellow laser is still seldom reported, and the above reported yellow laser emissions more focus on the 588 and 586.5 nm wavelength.…”
Section: Introductionmentioning
confidence: 99%
“…Shortly thereafter, they demonstrated a 586.5 nm CW yellow source based on self-Raman laser operation in Nd:GdVO 4 [16,17]. Recently N. Landru et al reported low noise Raman lasers for yellow-orange spectrum coverage from 556 nm up to more than 610 nm [18]. But because of the high SRS threshold, the CW intracavity SRS yellow laser is still seldom reported, and the above reported yellow laser emissions more focus on the 588 and 586.5 nm wavelength.…”
Section: Introductionmentioning
confidence: 99%